Do We Belittle Essential Tremor by Calling It a Syndrome Rather Than a Disease? No - Elble, Rodger J. (Frontiers in Neurology, 2020)
A task force of the International Parkinson and Movement Disorder Society (MDS) recently published a tremor classification scheme that is based on the nosologic principle of two primary axes for classifying an illness: clinical manifestations (Axis 1) and etiology (Axis 2). An Axis 1 clinical syndrome is a recurring group of clinical symptoms, signs (physical findings) and possibly laboratory results that suggest the presence of at least one underlying Axis 2 etiology. Syndromes must be defined and used consistently to be of value in finding specific etiologies and effective treatments. The MDS task force concluded that essential tremor is a common neurological syndrome that has never been defined consistently by clinicians and researchers. The MDS task force defined essential tremor as a syndrome of bilateral upper limb action tremor of at least 3 years duration, with or without tremor in other locations (e.g., head, voice, or lower limbs), in the absence of other neurological signs (e.g., dystonia, parkinsonism, myoclonus, ataxia, peripheral neuropathy and cognitive impairment). Deviations from this definition should not be labeled as essential tremor. Patients with additional questionably-abnormal signs or with signs of uncertain relevance to tremor are classified as essential tremor plus. The MDS classification scheme encourages a thorough unbiased phenotyping of patients with tremor, with no assumptions of etiology, pathology, pathophysiology or relationship to other neurological disorders. The etiologies, pathology and clinical course of essential tremor are too heterogeneous for this syndrome to be viewed as a disease or a family of diseases.